2016
DOI: 10.1021/acs.joc.6b02152
|View full text |Cite
|
Sign up to set email alerts
|

Photocaging of Single and Dual (Similar or Different) Carboxylic and Amino Acids by Acetyl Carbazole and its Application as Dual Drug Delivery in Cancer Therapy

Abstract: A new fluorescent photoremovable protecting group (FPRPG) based on acetylcarbazole framework has been explored for the first time release of single and dual (similar or different) substrates from single chromophore. Mechanistic studies of the photorelease process revealed that photorelease of two (similar or different) substrates from acetyl carbazole proceeds via a stepwise pathway. Further, we constructed photoresponsive dual drug delivery system (DDS) to release two different anticancer drugs (caffeic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
0
39
0
Order By: Relevance
“…Based on our earlier studies, DFT calculations, and solvent study on photorelease, we suggested a possible mechanism for the photorelease of dual‐arm caged compounds ( 8a–c , 11d – f , and 13 ) as shown in Scheme . The initial photochemical step involves excitation of the dual‐arm caged compound 8a to its singlet excited state (S1), which then undergoes intersystem crossing (ISC) to the triplet state (T1).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Based on our earlier studies, DFT calculations, and solvent study on photorelease, we suggested a possible mechanism for the photorelease of dual‐arm caged compounds ( 8a–c , 11d – f , and 13 ) as shown in Scheme . The initial photochemical step involves excitation of the dual‐arm caged compound 8a to its singlet excited state (S1), which then undergoes intersystem crossing (ISC) to the triplet state (T1).…”
Section: Resultsmentioning
confidence: 91%
“…PRPG 3 and the corresponding dual‐arm caged compounds [combination of carboxyl and hydroxyl ( 8a – c ), carboxyl and thiol ( 11d – f ), and carboxyl and amine ( 13 ) functionalities] were synthesized following a sequence of chemical reactions as shown in Scheme . Compound 1 was synthesized according to a known procedure . Next, 2 was obtained by heating 1 to reflux with sodium formate in ethanol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After radiation absorption, the photoprocesses that occur from the excited states of carbazole can find applications in areas of increasing current relevance such as sensitizing, sensing chemistry, electrochemistry and optical materials among others. [1][2][3][4][5][6] Since their relatively simple synthesis procedure and versatility in functionalization, carbazoles are excellent fragments for the design of hole transporters materials because they combine chemical robustness with electronically tunable properties. [7,8] Nowadays, the use of carbazoles in thermally activated delayed fluorescence (TADF) processes for development of the third generation of OLED technology is a featured topic in the optoelectronic devices field.…”
Section: Introductionmentioning
confidence: 99%
“…Among the stimuli responsive DDSs, noninvasive light stimulated DDSs have an edge over others as they can manipulate the rate of drug delivery process at targeted site by photocage (photocleavable unit caged bioactive molecule), which can be activated by specific wavelength. To date, several photoresponsive drug delivery systems for combination therapy have been reported …”
Section: Introductionmentioning
confidence: 99%